METHODS FOR STUDYING PERIODONTAL DISEASES IN WOMEN IN THE POSTMENOPAUSE PERIOD - Gubaev Mukhiddin Sarimsokovich, (Лучшие интеллектуальные исследования, 2024)
Annotation. Much attention is paid to the relationship between the menopause and the pathology of other organs and systems. A study of the dental status of menopausal women has proven the existence of a relationship between a decrease in estrogen concentrations and a sharp increase in dental diseases. Since the oral mucosa contains estrogen receptors, hormonal changes can be manifested by the progression of dental diseases such as caries, gingivitis, periodontitis, as well as changes in the oral mucosa: burning, bad taste in the mouth, saliva viscosity, dry mouth.